MODEL PENGEMBANGAN USAHA KECIL DAN MENENGAH BERBASIS SINERGITAS MULTI STAKEHOLDERS - Muhammad Tahwin; Anik Nurhidayati (STIE Pelita Nusantara Semarang, 2021)
This research aim is to formulate multy-stakeholder synergy model to develop Batik Tulis Lasem Industry. The research object is Batik Tulis Lasem Industry, in Rembang Regency. Data collecting method used is questioner and interview. The sampling technique used is purposive sampling. Analyzing data used is SWOT and triple helix concept. The research result shows that there are twenty two strategic formulas in SWOT matrix, they are six strategy formulations of S-O strategy, seven strategy formulations of S –T strategy, three strategy formulations and six strategy formulations of W-T strategy. Based on the strategic formulation in SWOT matrix, the results are fifteen triple helix perspective strategy formulas, they are five strategy formulations of S-O strategy, four strategy formulations of S-T strategy, two strategy formulations of W-O strategy, and four strategy formulations of W-T strategy. The strategy formulations are the multi-stakeholder synergy model as the collaboration of the government, college and industry to develop Batik Tulis Lasem.